The activity of the society «Ridna Shkola» («Native School») in Tysmenytsia town (1906 – 1939) - Andrii Korolko; Igor Fedoryshyn (Cхід, 2019)
The activity of “Native School” association in Tysmenytsia Tovmatsky district based on the archive sources and scientific works during Austrian and inter-war period was highlighted in the issue. The main attention was paid to the circle’s activity in Tysmenytsia, the educational, cultural and public work was characterized, the statistical data about its quantity was provided. The educational, cultural and public work of “Native School” institution was depicted through the lectures and reports conducting, concerts, children entertainments’ performance, plays staging, kindergartens’ organization, and custody of the children. Moreover, the circle’s cooperation with other Ukrainian cultural and educational associations was demonstrated, in particular with the local institution of “Prosvita”, for the library of which the members of “Native School” organization in Tysmenytsia purchased the educational and fiction literature. Notwithstanding the association positioned itself as a non-party organization, there was an inter-party struggle for the influence on it. “Native School” institution in Tysmenytsia was of interest to the local organizations of the Ukrainian Radical Party, the Ukrainian National Democratic Association, and the Organization of Ukrainian Nationalists at some historical periods. Contrary to the policy of pacifism and polonization provided by the Polish government against the Ukrainians, the circle of “Native School” sustained the pressure of the authorities, enhanced educational work in the town and provided fruitful cooperation with the Main administration in Lviv and the District union of the circles in Tovmach and Stanyslaviv, became one of the most effective Ukrainian educational organizations in the town in the 1930-s. “Native School” was forbidden and the circle in Tysmenytsia was closed as the hundreds of others with the Soviet authorities’ establishment in the territory of Western Ukraine in 1939.